Law, Order and Riots in Mandatory Palestine, 1928-35 - Kolinsky, M. author. aut Link
XX, 295 p.
Keywords: Political and legal order in Palestine was severely shaken by the rioting of August 1929 and 1933. As Britain struggled to find a balance between Arab and Jewish demands the middle years of the Mandate proved to be crucial for the survival of the Jewish National Home. The period was also highly significant for the development of the Palestinian Arab nationalist movement, and for the shaping of British policy in response to the emerging international issues which threatened its hegemony in the Middle East.